Verifikasi Dosis Rekomendasi Pemupukan Hara Spesifik Lokasi untuk Padi Varietas Hibrida - Suyamto, Suyamto; Saeri, M.; Saraswati, D. P.; Robi’in, Robi’in (Pusat Penelitian dan Pengembangan Tanaman Pangan, 2015)
IAARD in collaboration with IRRI has developed site specific nutrient management (SSNM or PHSL) recommendation, which can be accessed through PHSL-web (http:/webapps.irri.org/nm/id). PHSL recommendations were evaluated for inbred rice variety but not yet for hybrid rice. The objective of this experiment was to verify the effectiveness of PHSL recommendation for hybrid rice and to evaluate the response of hybrid rice to N fertilizer. Two experiments were conducted during the dry season of 2012 in two locations (Malang and Blitar). The first experiment consisted of 6 treatments: (1) PHSL recommendation based on yield target of hybrid variety (Mapan-P05) (10.3 t/ha or 20% higher compared to that of inbred variety), (2) same as treatment 1 for Hipa-10 hybrid variety, (3) same as treatment 1 for Ciherang variety, (4) PHSL based on the yield target similar to that of inbred variety (8.6 t/ha) applied for Mapan-P05 hybrid variety, (5) same as treatment 4 applied for Hipa-10 hybrid variety, and (6) same as treatment 4 applied for Ciherang inbred variety. PHSL recommendation for hybrid rice was 300 kg NPK (Phonska) + 376 kg urea/ha applied 4 times, while that for inbred rice was 200 kg NPK (Phonska) + 332 kg urea/ha applied 3 times. The experiment was arranged in a randomized complete block design, 4 replications, and plot size was 5 m x 10 m. The second experiment was arranged in a split plot design with four replications and plot size 5 m x 10 m. The main plots consisted of 4 rates of urea application namely: 0; 150; 300; and 450 kg urea/ha. The sub plots were two varieties namely: Mapan-P05 (hybrid) and Ciherang (inbred). Soil was analyzed before the conduct of experiment. Main data collection included yield of rice, hybrid rice respon to urea fertilizer. Results of the experiment showed that fertilizer rate based on PHSL for hybrid rice was not appropriate. Applying rate of fertilizers based on PHSL for hybrid rice resulted in rice yields not significantly different to that of inbred variety fertilized based on PHSL for inbred variety. The response of hybrid variety to N fertilizer was higher than that of inbred variety, suggesting that hybrid rice produced higher yield than did inbred, at the same rate of fertilizer. To obtain a higher yield of hybrid rice (such as Mapan-P05) the rate and time of fertilizer applications are not necessarily to be increased as recommended on PHSL-web. Using the same fertilizer rate, hybrid rice (such as Mapan-P05) produced higher yield compared to that of inbred variety, which indicated higher efficiency of fertilization. Yield of hybrid rice Hipa-10 variety was not only determined by fertilizer rate but also by other factors, such as seed quality and crop management (M). The existence of GxExM interaction was higher for hybrid rice, meaning hybrid variety required very specific environment.Keywords:Â